2016
DOI: 10.1039/c6dt01625a
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic DFT and experimental studies of mono- and bis-actinyl complexes of an expanded Schiff-base polypyrrole macrocycle

Abstract: The computationally- and experimentally-determined molecular structures of a bis-uranyl(vi) complex of an expanded Schiff-base polypyrrolic macrocycle [(UO)(L)] are in close agreement only if the pyridine in the fifth equatorial donor site on the uranium is included in the calculations. The relativistic density functional theory (DFT) calculations presented here are augmented from those on previously reported simpler frameworks, and demonstrate that other augmentations, such as the incorporation of condensed-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…Coordination of an electropositive metal within the vacant compartment of the macrocycle was shown to activate the uranyl towards reduction so forming a range of stable mixed-metal, [U V O 2 ] + com-plexes. 10,11 The anthracenyl linker enforces both a greater distance between the N 4 -coordination compartments and a greater degree of coplanarity. Fe(II), Mn(II)) did not promote reduction and the corresponding uranyl(VI) U VI O 2 M(L Me ) complexes were isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Coordination of an electropositive metal within the vacant compartment of the macrocycle was shown to activate the uranyl towards reduction so forming a range of stable mixed-metal, [U V O 2 ] + com-plexes. 10,11 The anthracenyl linker enforces both a greater distance between the N 4 -coordination compartments and a greater degree of coplanarity. Fe(II), Mn(II)) did not promote reduction and the corresponding uranyl(VI) U VI O 2 M(L Me ) complexes were isolated.…”
Section: Introductionmentioning
confidence: 99%
“…And their formation reaction energetics was addressed, particularly for the uranyl complexes where the single pyridine coordinated [(py)(U VI O 2 ) 2 (L)] (B‐( s ‐ py)U VI ) and the pyridine‐free [(U VI O 2 ) 2 (L)] (B‐ U VI ) and [(U VI O 2 )(H 2 L)] (M‐ U VI ) were added for comparison. This work complements our recent work that focuses on the synthesis and characterization from experiment (for U) and the structural optimization from computation (U, Np, and Pu).…”
Section: Computational Detailsmentioning
confidence: 55%
“…Our previous theoretical study suggested that the penta valent uranyl bar is less rigid than the hexa valent one and more easily transformed to the cis ‐structure. Experimentally, Arnold and Love et al have chemically modified the aryl‐linked H 4 L Ar ligand and prepared an anthracenyl‐containing polypyrrolic macrocycle (H 4 L, Chart ) that has longer linker . The enlarged space allows the ligand H 4 L to complexate two trans ‐uranyl(VI) rods .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations